Matrix Solid-Phase Dispersion Combined with HPLC-DAD for Simultaneous Determination of Nine Lignans in Saururus chinensis. (1st October 2018) - Chen, Hongjiang; Ji, Tao; Chen, Jianwei; Li, Xiang
Abstract: A simple and rapid method, based on matrix solid-phase dispersion (MSPD) and high-performance liquid chromatography (HPLC) was developed for simultaneous determination of nine lignans, including (-)-(7 R, 8 R )-machilin D (Wang, C., Wang, P., Chen, X., Wang, W., Jin, Y.; Saururus chinensis (Lour.) Baill blocks enterovirus 71 infection by hijacking MEK1-ERK signaling pathway; Antiviral Research, (2015); 119:47–56), dihydroguaiaretic acid (Quan, Z., Lee, Y.J., Yang, J.H., Lu, Y., Li, Y., Lee, Y.K., et al.; Ethanol extracts of Saururus chinensis suppress ovalbumin-sensitization airway inflammation; Journal of Ethnopharmacology, (2010); 132:143–149.), sauchinone (Zhuang, T., Liang, J.Y., Sun, J.B., Wu, Y., Huang, L.R., Qu, W.; Secondary metabolites from Saururus chinensis and their chemotaxonomic significance; Biochemical Systematics and Ecology, (2014); 56:95–98.), rel -(7 S, 8 S, 7′ R, 8′ R )-3, 3′, 4, 4′, 5, 5′-hexamethoxy-7. O .7′, 8.8′-lignan (Tsai, W.J., Shen, C.C., Tsai, T.H., Lin, L.C.; Lignans from the aerial parts of Saururus chinensis: isolation, structural characterization, and their effects on platelet aggregation; Journal of Natural Products, (2014); 77:125–131), licarin A (Cui, H., Xu, B., Wu, T., Xu, J., Yuan, Y., Gu, Q.; Potential antiviral lignans from the roots of Saururus chinensis with activity against Epstein-Barr virus lytic replication; Journal of Natural Products, (2014); 77:100–110.), manassantin A (Lu, Y., Piao, D., Zhang, H., Li, X., Chao, G.H., Park, S.J., et al.; Saucerneol F inhibits tumor necrosis factor-alpha and IL-6 production by suppressing Fyn-mediated pathways in FcepsilonRI-mediated mast cells; Food and Chemical Toxicology, (2013); 59:696–702.), saurucinol I (Kwon, O.E., Lee, H.S., Lee, S.W., Chung, M.Y., Bae, K.H., Rho, M.C., et al.; Manassantin A and B isolated from Saururus chinensis inhibit TNF-α-induced cell adhesion molecule expression of human umbilical vein endothelial cells; Archives of Pharmacal Research, (2005); 28:55–60.), manassantin B (Hwang, B.Y., Lee, J.H., Jung, H.S., Kim, K.S., Nam, J.B., Hong, Y.S., et al.; Sauchinone, a lignan from Saururus chinensis, suppresses iNOS expression through the inhibition of transactivation activity of RelA of NF-κB; Planta Medica, (2003); 69:1096–01.) and licarin B (Hwang, B.Y., Lee, J.H., Nam, J.B., Hong, Y.S., Lee, J.J.; Lignans from Saururus chinensis inhibiting the transcription factor NF-κB; Phytochemistry, (2003); 64:765–771.) in Saururus chinensis . The parameters of MSPD were optimized to be that 0.2 g of sample, blended with 0.4 g silica gel, and eluted with 5 mL of methanol. The separation was carried out on a C18 column with acidified aqueous acetonitrile gradients. The established method was fully validated in terms of linearity ( r 2 ≥ 0.9994), sensitivity, precision (RSD ≤ 3.18%), repeatability (RSD ≤ 3.02%) as well as recovery (93.49–103.52%), and subsequently applied to six samples of S. chinensis from different areas. The MSPD extraction promoted higher extraction yields of nine lignans, lower solvent sample and solvent consumption.